2016
DOI: 10.1021/acschembio.5b00923
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyphenylation of Histone Lysines: Post-translational Modification by Quinone Imines

Abstract: Monocyclic aromatic amines are widespread environmental contaminants with multiple sources such as combustion products, pharmaceuticals, and pesticides. Their phenolic metabolites are converted intracellularly to electrophilic quinone imines upon autoxidation and can embed in the cellular matrix through a transimination reaction that leaves a redox-active residue as a substituent of lysine side-chain amino groups. To demonstrate the occurrence of this process within the cellular nucleus, Chinese hamster ovary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Halobenzoquinones were also confirmed to be of high cytotoxicity and induced reproductive and developmental toxicity . Semiquinone-free radicals of HQCs may cause the production of ROS, further cause DNA damage or combine with the mercapto groups of histones and subsequently integrate into proteins to form adducts in living cells. Levels of intracellular ROS at the concentration of IC 50 in HepG2 cells after a 24 h exposure to five HQCs are shown in Figure S4. It is shown that all five tested HQCs exhibited the ability to generate ROS, which partially supported that excessive production of ROS in HepG2 cells may be one of the mechanisms causing cytotoxicity of HQCs.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Halobenzoquinones were also confirmed to be of high cytotoxicity and induced reproductive and developmental toxicity . Semiquinone-free radicals of HQCs may cause the production of ROS, further cause DNA damage or combine with the mercapto groups of histones and subsequently integrate into proteins to form adducts in living cells. Levels of intracellular ROS at the concentration of IC 50 in HepG2 cells after a 24 h exposure to five HQCs are shown in Figure S4. It is shown that all five tested HQCs exhibited the ability to generate ROS, which partially supported that excessive production of ROS in HepG2 cells may be one of the mechanisms causing cytotoxicity of HQCs.…”
Section: Resultsmentioning
confidence: 97%
“…25,26 HQCs could also react with the sulfhydryl groups of histones as electrophiles and integrate into proteins to form adducts. 27 The octanol−water partition coefficients of HQCs increased as a function of the halogen substitution degree, which indicated that HQCs were more difficult to be metabolized and excreted in organisms than quinone imines. 28 We calculated the toxicity of HQCs using computational toxicology software EPI Suite, which was developed by the US National Environmental Protection Agency and the US Syracuse Research Corporation, and widely used for predication of toxicity.…”
Section: ■ Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…9 Structures of study compounds used and of putative quinonoid oxidation intermediates hypothesised to be involved in the induction of Degs1 polyubiquitination en route to hydroxycelecoxib (Fig. 9, Box 2), which is a known metabolite [24][25][26][27][28][29]. In principle, protonation and dehydration of the latter might also generate an intermediate pyrazolium species with quinone methide character (Fig.…”
Section: Compound Structure-function Analysismentioning
confidence: 99%
“…9, Box 2). Quinone imines and related quinonoid species are redox-active entities and also have the potential to covalently modify biomolecular targets [24][25][26][27][28][29]. In this regard it is interesting that acetaminophen, which is known to generate N-acetyl-p-benzoquinone imine as a potentially toxic metabolite in vivo [30,31], does not induce polyubiquitination of Degs1 whereas the longer chain counterpart, 4-HPA, does induce polyubiquitination.…”
Section: Compound Structure-function Analysismentioning
confidence: 99%